2021
DOI: 10.3390/coatings11121476
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Multilayer Perceptrons Model Using Grey Wolf Optimizer to Predict Mechanical and Microstructural Properties of Friction Stir Processed Aluminum Alloy Reinforced by Nanoparticles

Abstract: In the current investigation, AA2024 aluminum alloy is reinforced by alumina nanoparticles using a friction stir process (FSP) with multiple passes. The mechanical properties and microstructure observation are conducted experimentally using tensile, microhardness, and microscopy analysis methods. The impacts of the process parameters on the output responses, such as mechanical properties and microstructure grain refinement, were investigated. The effect of multiple FSP passes on the grain refinement, and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…To overcome this challenge, more complex neural network structures or hybrid approaches (see refs. [ 24 , 33 , 34 ]) should be applied instead of basic neural networks or interpolation algorithms. Also, like computational simulations, the computing time and cost are limits for the metamodel process, especially for products with a high number of design variables.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this challenge, more complex neural network structures or hybrid approaches (see refs. [ 24 , 33 , 34 ]) should be applied instead of basic neural networks or interpolation algorithms. Also, like computational simulations, the computing time and cost are limits for the metamodel process, especially for products with a high number of design variables.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal cutting conditions that minimize the cutting forces and surface roughness could be determined metaheuristic approaches [ 37 , 38 , 39 , 40 ]. The process responses could be also predicted using artificial intelligence tools [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…They also revealed that if a wide range of machining conditions will be adopted, better results can be predicted through this method. Khoshaim et al (2021) predicted both mechanical and micro-structural properties of friction stir processed aluminium reinforced material using Grey Wolf optimizer. The input parameters are rotational speed, linear processing speed and number of passes, while the outputs were grain size, aspect ratio, micro-hardness and ultimate tensile strength.…”
Section: Introductionmentioning
confidence: 99%